EVALUASI PELAKSANAAN KEBIJAKAN UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN DALAM PENGGUNAAN HELM BERSTANDAR SNI DI KOTA SEMARANG - Raja Danial Kamarullah; Aufarul Marom (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
Policy Legislation Number 22 Year 2009 regarding Traffic and Transportation in the Application of Standards SNI Helmet in Semarang is one of the government's efforts to cope with the level of accidents that occur due to the use of helmets. The focus and main objectives of this policy are Indonesian citizens without being limited lifespan. Evaluation of this policy to see the results, driving and inhibiting factors in the implementation of the policy by using the policy evaluation indicators by William Dunn, namely: effectiveness, adequacy, responsiveness and appropriateness. Evaluation of Policy Implementation Legislation Number 22 Year 2009 regarding Traffic and Transportation In The Application of Standard SNI Helmet in Semarang in the indicators of the evaluation, two of them still considered the maximum that is based on the adequacy and responsiveness, while the assessment is good in the evaluation indicators effectiveness and appropriateness. Obstacles to Implementation of Standards SNI Helmet in Semarang is the lack of knowledge and understanding of the usefulness of the helmet. Other inhibiting factors in the program are given the uneven dissemination throughout the community. The results showed that the application of Standards SNI Helmet in Semarang is not maximized. The recommendation to the program like socializing more evenly, better understanding of the use of safety helmets, clarified and reinforced sanctions.